Impact of diabetes on outcomes of cardiac surgery in a multiethnic Southeast Asian population. (November 2019) - Moorthy, Vikaesh; Liu, Weiling; Chew, Sophia Tsong Huey; Ti, Lian Kah
Although diabetes is rapidly increasing in Asia and has been shown to be associated with worse cardiac surgery outcomes, no research has been done to study the impact of diabetes on cardiac surgery outcomes in a Southeast Asian cohort. Hence, this study aims to delineate the predictors and impact of diabetes after cardiac surgery in a multi-ethnic Southeast Asian cohort. We analysed data from 2831 adult patients undergoing elective cardiac surgery, from 2008 to 2010 in Singapore. Diabetes was found to significantly increase the odds of intensive care unit readmission by 1.70 (95% confidence interval 1.171–2.480, p = 0.005), postoperative infection by 1.73 (95% confidence interval 1.003–2.976, p = 0.049), acute kidney injury by 1.36 (95% confidence interval 1.137–1.626, p = 0.001), postoperative hyperglycaemia by 6.00 (95% confidence interval 4.893–7.348, p < 0.001), and new need for dialysis by 1.71 (95% 1.086–5.360, p = 0.021). In conclusion, diabetes is associated with increased risk for renal dysfunction, hyperglycaemia, and infection after cardiac surgery, similar to the relative risks of diabetes patients observed in Western populations.